IMPACT OF INTERNATIONAL POLITICAL RELATIONS ON THE COUNTRY'S ECONOMY - Abdurasulov Ravshanbek Hotam o‘g‘li (Scholar Express Journals, 2024)
This article covers Uzbekistan's role in the world community, its political relations with khaqlaro and the impact of these political ties on our country. The political problems that were taking place were studied and conclusions and suggestions were made
Keywords: International relations; political relations; exports